Exploring the Student Teaching Interns’ Journey in an Online Mode of Teaching Delivery (International Journal of Scientific Research and Management (IJSRM), 2022)
The COVID – 19 pandemic resulted in significant educational reforms. Even the once-in-a-lifetime face-to-face student teaching experience has been transformed into a virtual reality. The havoc caused by today’s difficulties prompted the creation of this article, which looked at the journey of student teaching interns as they completed online teaching demonstrations and other tasks as part of their student internship. Three sub-themes arose using Charmaz’s (2006) constructivist grounded theory: introspection as self-revelation, embracing the roles and responsibilities as student teaching interns, and integration as self-revelation. These sub-themes point to the meta-theme of student teaching interns’ molting phases as the theory. The theory describes the journey of student teaching interns as they face their fears via reflection, embrace the work at hand, and arrive at the stage of integration when they can be their best selves as teachers. Another investigation is necessary to assess the validity of the theory that arose from the research.